Trends in Research Librarianship Literature: A Social Network Analysis of Articles - Al, Umut; Soydal, İrem and Alir, Gülten (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2012)
The purpose of this article is to identify the bibliometric characteristics of research librarianship literature and to visualize relationships in research librarianship by means of social network analysis. It was found out that the majority (66%) of the articles had single authorship and College & Research Libraries is the prominent actor among the research librarianship journals. It was also observed that Peter Hernon is the most productive and cited author in the field. The findings of this study can be used by the research librarianship community to better understand their core literature.